BIOECOLOGICAL PROPERTIES OF CORN - Ismoilova Umida Ilg‘orovna; Norboeva Umida Toshtemirovna (Innovate Conferences, 2025)
Corn grows well, develops, and yields high yields when environmental factors are suitable for it. Therefore, it is important to correctly determine and adequately meet the environmental requirements of corn.Drought and soil salinity pose serious challenges to global agricultural production, posing a serious threat to food security and livelihoods.[1,2,3].The ongoing impact of climate change is leading to increased threats through more frequent occurrences of extreme weather events, such as long-term reductions in precipitation and increased soil salinity, among others [4.5].